University-Industry Linkage: Curriculum Support for Indonesia Islamic Economic Masterplan 2019-2024 (A Study in IAIN Gorontalo) - Nurul Fadhilah (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2024)
This research is conducted to disclose the role of Islamic economics education in university in term of its contribution to support the Indonesian Islamic economy masterplan 2019-2024. This study is conducted using qualitative approach, to elaborate the problems in Islamic Economic education provider in Indonesia. The case of IAIN Gorontalo as one of the providers of Islamic Economics education in Gorontalo is presented in this paper. The presented data are retrieved using library research. This study found that IAIN Gorontalo through the implemented curriculum is in line with the masterplan of Islamic Economic Masterplan 2019-2024. The courses in the existing curriculum are already relevant to support the national Islamic development planning. The challenge ahead for Indonesian Islamic economic education provider are to provide for the digital literate human resources and to encourage the entrepreneurship skill in the learning process.